Irish midwives' experiences of providing maternity care to non-Irish women seeking asylum - Tobin CL; Murphy-Lawless J (Dove Medical Press, 2014)
Carolyn L Tobin,1 Jo Murphy-Lawless2 1Department of Nursing, College of Health and Human Services, University of New Hampshire, Durham, NH, USA; 2School of Nursing and Midwifery, Trinity College, Dublin, Ireland Background: Immigration and asylum seeking has been an important social and political phenomenon in Ireland since the mid 1990s. Inward migration to Ireland was seen in unprecedented numbers from 1995 onward, peaking in 2002 with 11,634 applications for refugee status. Asylum and immigration is an issue of national and international relevance as the numbers of displaced people worldwide continues to grow, reaching the highest level in 20 years at 45.2 million in 2012. Midwives provide the majority of care to childbearing women around the world, whether working as autonomous practitioners or under the direction of an obstetrician. Limited data currently exist on the perspectives of midwives who provide care to childbearing women while they are in the process of seeking asylum. Such data are important to midwifery leaders, educators, and policy-makers. The aims of this study were to explore midwives' perceptions and experiences of providing care to women in the asylum process and to gain insight into how midwives can be equipped and supported to provide more effective care to this group in the future.Methods: Data were collected via indepth unstructured interviews with a purposive sample of ten midwives from two sites, one a large urban inner city hospital, and the second, a smaller more rural maternity hospital. The interviews were audio-recorded and transcribed verbatim. The data were analyzed using content analysis. Results: Five themes emerged from the data, barriers to communication, understanding cultural difference, challenges of caring for women who were unbooked, the emotional cost of caring, and structural barriers to effective care. Conclusion: Findings highlight a need to focus on support and education for midwives, improved maternity services for immigrant women, and urgent policy revision. Keywords: midwives, maternity care provision, Ireland, refugees, asylum process